ANALYSIS OF GCS AS A PREDICTOR OF MIDLINE SHIFT ON NCCT SCAN IN PATIENTS WITH ACUTE TRAUMATIC SUBDURAL HEMATOMA - Budiman; Evo Elidar Harahap; Abdurrahman Mousa Arsyad (PT. Radja Intercontinental Publishing, 2025)
The Glasgow Coma Scale (GCS) is commonly used to assess the severity of head trauma; however, it is not sufficiently accurate for predicting midline shift (MLS) without imaging support. This study aims to analyze the sensitivity and specificity of GCS in predicting MLS in patients with acute SDH. Subjects were patients diagnosed with acute traumatic SDH who underwent non-contrast head CT scans. Data were collected to assess the correlation between GCS scores and MLS values and to determine the GCS cut-off point for predicting MLS. Among 34 patients, the majority were male (76.5%) and aged between 18–34 years (35.3%). Most patients had a GCS score of 9–13 (38.2%) and showed subarachnoid hemorrhage on CT scan (44.1%). A strong correlation was found between lower GCS scores and increased MLS. The mean MLS increased significantly with decreasing levels of consciousness. The GCS cut-off score to differentiate significant MLS was 13, with a sensitivity of 100%, specificity of 79.3%, positive predictive value of 87%, and negative predictive value of 85%. GCS has a strong correlation with MLS and can be used as a reliable clinical indicator to predict MLS in patients with acute traumatic SDH.